PERENCANAAN INFORMATION TECHNOLOGY PROBLEM MANAGEMENT BERDASARKAN ITIL V3 PADA RSU HAJI SURABAYA - Prasetya, Candra Dwi; Slamet, Slamet; Maulana, Yoppy (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
RSU Haji Surabaya is a public hospital located in Manyar Kertoadi Street Surabaya of East Java Province Goverment. In the process of defining and grouping there are a lack in doing the steps of definition and grouping. The process of observing and diagnosing problems, inaccuracies in reducing or eliminating the impact of an error problem. The process of resolving the problem is not there is a solution that do if there damage over and over. The process of making management of the problem after done repair did prevention what can be done in order to avoid a similiar problem. So that the impact there is no clarity in doing management of the problem.In the process of repair the document planning, used the standart or best practice Infromation Technology Infrastructure Library (ITIL) Version 3 (V3) about Service Operation, especially related to the process of the Problem Management. The main focus on the problem management was chosen because it is an activity that is conducted to find out the cause of the problem, problem complete, reduce the risk, and avoid a recurrence of the same problem back on the installation SIMRS.The result of this research were obtained planning document IT problem management 8 Standart Operational Procedure (SOP), 9 (IK) Work Instructions and Work Record 22 (RK).